2012
DOI: 10.1007/s11605-012-1869-7
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Analysis of Pterostilbene Predicts Its Antiproliferative Effects Against Pancreatic Cancer In Vitro and In Vivo

Abstract: Background-To investigate the inhibitory role of pterostilbene in pancreatic cancer, we conducted a genomic analysis of pterostilbene-treated pancreatic cancer cells. We also investigated the effect of pterostilbene upon the carcinogenic markers, manganese superoxide dismutase, cytochrome C, Smac/DIABLO, and STAT3 phosphorylation in vitro. The antiproliferative effects of pterostilbene were further evaluated in an in vivo model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 17 publications
0
33
0
Order By: Relevance
“…Furthermore, PTE has been reported to decrease tumor size and prolong survival in tumor-inoculated mice [28,29,30]. In the present study, mice were administered 5% DMSO and saline or 50 mg/kg PTE via intraperitoneal injection for 14 days, resulting in a significant reduction in tumor volume with PTE treatment.…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, PTE has been reported to decrease tumor size and prolong survival in tumor-inoculated mice [28,29,30]. In the present study, mice were administered 5% DMSO and saline or 50 mg/kg PTE via intraperitoneal injection for 14 days, resulting in a significant reduction in tumor volume with PTE treatment.…”
Section: Discussionmentioning
confidence: 92%
“…In vivo, oral administration of pterostilbene at 100 mg/kg/d and 500 mg/kg/d significantly inhibited tumor growth rates in xenograft mouse models without producing signs of acute toxicity. [24]. These are doses much lower than previously described in animal models.…”
Section: Pancreasmentioning
confidence: 84%
“…Pterostilbene inhibits cell proliferation and promotes apoptosis in pancreatic cancer in vitro through a mitochondrially-derived mechanism of apoptosis that includes mitochondrial membrane depolarization, release of the mitochondrial proteins cytochrome c and Smac/DIABLO with subsequent activation of caspase 3/7 [24,25], It has also been shown that pterostilbene promotes apoptosis in the pancreatic cancer cell line MIA PaCa-2 through up and down-regulation of multiple apoptosis-related genes, including manganese superoxide dismutase (MnSOD), DNA-damage-inducible transcript 3 (DDIT-3), and growth differentiation factor 15 (GDF-15), also known as macrophage inhibitory cytokine 1 (MIC-1) [24]. Furthermore, pterostilbeneinduced up-regulation of MnSOD also translated into increased enzymatic activity within the mitochondria, further indicating a mitochondrially-derived mechanism of pterostilbene.…”
Section: Pancreasmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that pterostilbene inhibits pancreatic cancer in vitro and in vivo through mechanisms of mitochondrially derived apoptosis, modification of transcription factors, and inhibition of proliferation [63, 64]. Specifically, pterostilbene-induced apoptosis in the pancreatic cell lines MIA PaCa-2 and PANC-1 has been attributed to mitochondrial membrane depolarization, release of Cytochrome C, and Smac/DIABLO with subsequent activation of caspase 3/7 [63, 64].…”
Section: Antioxidant Properties Of Pterostilbenementioning
confidence: 99%